Integrative approach to characterize new mechanisms of toxicity of pollutants in Daphnia magna - Jordão, Rita Marisa Gomes (2017)
In the last decades, the scientific community focused on the study of the toxicity of persistent and widely distributed chemical pollutants in the aquatic environment. Typically, complex mixtures of priority pollutants, emerging substances, transformation products and/or natural compounds co-occur in aquatic systems, thus rendering the risk assessment a challenge. The current standard toxicity assays such as those based on acute and chronic responses may not be sensitive enough to detect the contaminant effects at low environmentally relevant concentrations. Thus, the development of new assessment tools and new conceptual approaches is essential. Therefore, the aim of this thesis is to elucidate novel mechanisms of action of toxicity in aquatic invertebrate species using the crustacean Daphnia magna as a model organism. For that, standard assays combined with new approaches were used for the analysis of specific sub-lethal effects and health consequences of emerging and classical pollutants. The work was developed around two main topics; the characterization of obesogenic effects produced by endocrine disruptors and as well, the characterization of the multixenobiotic resistance mechanisms in tolerant clones of the D. magna. With the obtained results we observed endocrine disrupting effects on the lipid metabolism of D. magna when exposed to emerging and classical compounds, activating the ecdysone, the juvenil hormone and RXR receptor signalling pathways. One of the key features of endocrine disruption, including obesogenic effects, was to adversely affect offspring quality and its latter performance during its life cycle. Moreover, in the second topic we observed evidences of a close association between general stress responses and multixenobiotic resistance mechanisms in tolerant clones of D. magna and that both mechanisms are genetically co-selectable. In conclusion, this thesis presents, for the first time, obesogenic efects in D. magna and that multixenobiotic resistance mechanisms can be part of a general mechanism of tolerance, key to cope with environmental stress.